GIJOUGO DALAM MANGA GREAT TEACHER ONIZUKA KARYA TORU FUJISAWA - Candra Erdika, I Kadek Amerta; Luhur Wedayanti, Ni Putu; Budiana, I Made (Humanis; Volume 16. No. 1. Juli 2016)
This research is entitled “Gijougo in Great Teacher Onizuka Comic by Toru Fujisawa”. This research discuss about using and meaning of Gijougo in Great Teacher Onizuka Comic. The main theory used in the analysis  were Morfology Theory by Tsujimura (1999), Syntax Theory by Chaer (2009), and Semantic Theory by Pateda (2001). The analysis in this paper shows that in all 26 datas, there are 18 kind of gijougo in Great Teacher Onizuka Comic. From all that data, gijougo is mostly used as a verb in a sentence and not every grammatical process changes the gijougo meaning, but some gijougo’s meaning are changed too.
Keywords: Gijougo, Using, Meaning